2007
DOI: 10.1177/0146167206293492
|View full text |Cite
|
Sign up to set email alerts
|

Personalized and Generalized Comparisons: Causes and Consequences of Variations in the Focus of Social Comparisons

Abstract: When people compare with another person they can focus on how they compare either with just that target (a personalized comparison) or with others more generally (a generalized comparison). Four studies (two event-contingent diary studies, one study of comparisons during a triathlon, and one controlled experiment) showed that personalized comparisons were more likely when the target’s attribute was distinctive or there was an interaction or a close or emotional relationship with the target. Perhaps because the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 48 publications
2
26
1
Order By: Relevance
“…Comments about "constantly rating, judging, comparing, or sizing people up," during and, retrospectively, before the diary period, were commonplace. These data contrast sharply with reports of approximately one to two comparisons per day, on average, provided by participants in other diary studies (Antony et al, 2005;Bogart et al, 2004;Locke, 2007;Patrick et al, 2004). The discrepancy may be accounted for by the possibility that individuals in the present study were more motivated to follow the study procedure (because this was a voluntary part of the course curriculum) and more introspectively sophisticated (because they were largely psychology majors who also received brief mindfulness training) than those in other studies.…”
Section: Discussioncontrasting
confidence: 97%
“…Comments about "constantly rating, judging, comparing, or sizing people up," during and, retrospectively, before the diary period, were commonplace. These data contrast sharply with reports of approximately one to two comparisons per day, on average, provided by participants in other diary studies (Antony et al, 2005;Bogart et al, 2004;Locke, 2007;Patrick et al, 2004). The discrepancy may be accounted for by the possibility that individuals in the present study were more motivated to follow the study procedure (because this was a voluntary part of the course curriculum) and more introspectively sophisticated (because they were largely psychology majors who also received brief mindfulness training) than those in other studies.…”
Section: Discussioncontrasting
confidence: 97%
“…In addition, the results suggest that the generalized other (the class) has a more significant influence on students than do comparisons with individuals. These findings support the work of Locke () and suggest that the generalized other produces a broader understanding of the self rather than comparing with an individual, which may reflect a more restricted view of the self. These results supported our prediction that the higher the PRSC was, the higher individuals’ PSC was (Chanal & Sarrazin, ).…”
Section: Discussionsupporting
confidence: 87%
“…The importance of different frames of reference has been investigated in other areas of psychology as well. In an examination of personalized and generalized comparisons, Locke () found that the emotional consequences of generalized comparisons were greater (when an upward comparison was engaged in) than those of personalized comparisons. Locke suggests that this is due to the restrictive nature of personalized comparisons, whereas those comparisons that are more generalized expand the relevance of comparison information and, therefore, have a bigger impact on an individual.…”
Section: Frames Of Referencementioning
confidence: 99%
“…Such comparisons are not representative of the spontaneous comparisons people make in the course of their everyday lives (Locke & Nekich, 2000). Of particular relevance to the current investigation is the finding that in at least two thirds of naturally occurring social comparisons the targets are known others, and most of these known targets are friends and relatives (Locke, 2003(Locke, , 2007. Findings from studies of constrained comparisons with strangers may not always generalize to these more complicated comparisons with known targets-people with whom there are preexisting feelings and interdependencies-that populate everyday life.…”
Section: Relationship Variables Moderate Ability Judgmentsmentioning
confidence: 94%
“…Studies of naturally occurring social comparisons have shown that more than two thirds of comparisons are personalized comparisons in which the comparer's main concern is ''How do I compare particularly with this one person'' rather than ''How do I compare with others in general'' (Locke, 2007). Personalized comparisons occur more often when the comparer feels close to or strongly about the target and when the target's attribute is distinctive, presumably because these conditions prompt the comparer to focus on the target as a distinct individual (Locke, 2007). Alicke et al (1997) proposed that ''exaggerating the outperformer's ability is a construal mechanism that negates the potentially negative implications of unfavorable social comparisons by allowing inferior performers to discount the relevance of the comparison'' (p. 782).…”
Section: Relationship Variables Moderate Ability Judgmentsmentioning
confidence: 99%